Mucoadhesive polymers and their mode of action: a recent update - Chatterjee, Bappaditya; Amalina, Nursazreen; Mandal, Uttam Kumar; Sengupta, Pinaki (Journal of Applied Pharmaceutical Science, 2017)
The potential of mucoadhesive delivery system for sustained delivery of drug has been established few decades back. Different polymeric systems such as single or combined, substituted, conjugated, pre-activated polymer (s) etc. are used to develop such delivery platform. To explain the mucoadhesion mechanism, several possible theories namely electronic theory, adsorption theory, wetting theory, diffusion theory, fraction theory and mechanical theory has been proposed. But none of these theories alone can explain the mechanism of mucoadhesion. Various mechanism of mucoadhesion or bioadhesion between polymer and mucin such as H bonding, electrostatic interactions, di-sulfide linkage, van Der Waals attraction etc have been evidenced. Researches are focused to enrich such interaction between the mucous layer and the delivery platform by modifying the system. Wide varieties of polymers such as cationic, anionic, non-ionic, thiolated polymers etc have been used to design and develop mucoadhesive drug delivery system. Therefore reviewing and analyzing the mucoadhesive polymeric system and their mechanism of action is still relevant and necessary. The aim of this current review is to highlight the polymers which are being used under recent scientific researches with emphasis on their mechanism of mucoadhesion. The outcome of this review will help researchers to screen the mucoadhesive polymers for their intended use.